Improve Filter Backwash Performance With Process Testing. Issue 11 (31st October 2018) - Brewer, Todd F.; Linder, Kevin
Abstract : As an essential component of the multibarrier approach to safe drinking water, filtration represents the core of the Partnership for Safe Water's Treatment Optimization Program.